Establishing trust in offshore software outsourcing relationships: an exploratory study using a systematic literature review. Issue 5 (1st October 2013) - Niazi, Mahmood; Ikram, Naveed; Bano, Muneera; Imtiaz, Salma; Khan, Siffat Ullah
Abstract : Offshore software outsourcing is a widely used business strategy for producing high‐quality software at low cost. Trust plays a vital role in establishing the offshore software outsourcing relationships between client and vendor organisations. The objective of this research study is to identify factors via systematic literature review (SLR) that are important for establishing trust in offshore software outsourcing relationships. The authors have performed an SLR by applying the customised search strings, which were derived from the research questions. The authors have identified factors such as face‐to‐face meeting, better communication, contract management between client and vendor, defining processes, tools, procedures and policies, reliable management, knowledge sharing, mutual expectations, better client‐vendor relationship and training programmes that are generally considered critical for establishing trust in offshore software outsourcing relationships. The results also reveal the similarities and differences in the factors identified through different study strategies and in different continents. Offshore software outsourcing companies should focus on the frequently cited factors in order to compete in the offshore software outsourcing business.